Hepatic arterial infusion chemotherapy combined with immune checkpoint inhibitors and molecular targeted therapies for advanced infiltrative hepatocellular carcinoma: a single-center experience - Wang, Zizhuo; Song, Songlin; Zhang, Lijie; Yang, Tingting; Yao, Wei; Liang, Bin (Frontiers in Immunology, 2025)
BackgroundInfiltrative hepatocellular carcinoma (HCC) remains a therapeutic challenge due to its aggressive course and poor prognosis. Hepatic arterial infusion chemotherapy (HAIC) plus immune checkpoint inhibitors (ICIs) and molecular targeted therapies (MTTs) has shown early promise for advanced HCC, but its role in advanced infiltrative HCC is unclear. This study aims to investigate the efficacy and safety of HAIC combined with ICIs and MTTs in the treatment of advanced infiltrative HCC.MethodsPatients with infiltrative HCC initially treated with HAIC plus ICIs and MTTs were consecutively included at our institution from November 2021 to June 2023. The efficacy evaluation included tumor response, time to response (TTR), duration of response (DOR), progression-free survival (PFS) per RECIST 1.1, and patient survival. Adverse events (AEs) were recorded for safety evaluation.ResultsA total of 27 patients were included and the median follow-up was 15.8 months (range, 4.3–25.9). The best objective response rate (ORR) and disease control rate (DCR) were 70.4% and 88.9%, respectively. The median TTR was 2.8 months (95% confidence interval [CI], 2.6–3.0) and the median DOR was 7.9 months (95% CI, 3.2–12.5). The median PFS was 7.5 months (95% CI, 4.2–10.7), and the median overall survival (OS) was 16.8 months (95% CI, 14.0–19.6), with a 1-year OS rate of 74.1%. No cases of grade 4 or 5 treatment-related adverse events (TRAEs) were observed in this study. Grade 3 TRAEs occurred in 17/27 (63.0%) patients, and the predominant grade 3 treatment-related adverse events were lymphocyte count decreased (18.5%) and neutrophil count decreased (14.8%).ConclusionsThe combination of HAIC plus ICIs and MTTs demonstrated encouraging outcomes and manageable safety concerns for infiltrative HCC.